Easy-to-use EEG data collection platform for motor imagery - Qi, Hang (Nanyang Technological University, 2023)
Brain-Computer Interface (BCI), as a novel form of human-computer interaction, holds great potential to revolutionize the world. Among various BCI paradigms, the Motor Imagery-based Electroencephalogram (MI-EEG) BCI stands out as a non-invasive method that allows for the control of external devices such as robots solely through the power of imagination, without the need for external stimulation.